Strengthening collaboration within Dutch municipalities for a healthier living environment: experiences and possible improvements according to civil servants - Mourits, Kristine; Spitters, Hilde; van der Velden, Koos; Bekker, Marleen; Molleman, Gerard (Frontiers in Public Health, 2024)
Background: Health is partly determined by the physical environment in which people live. It is therefore crucial to consider health when designing the physical living space. This requires collaboration between the social and physical domains within municipalities. Collaboration is not self-evident, however, and it is difficult to achieve due to barriers relating to culture, language and work processes. Additionally, improvements in collaboration are desperately needed to address complex health issues, and working according to the new Environment and Planning Act in the Netherlands requires more collaboration. One relevant question concerns how civil servants describe the current collaboration between the social and physical domain and the concrete improvements they propose to improve such collaboration to build a healthier living environment. Methods: In this qualitative study, the Collaborative Governance framework was used to present data from semi-structured interviews with 21 civil servants in five Dutch municipalities. Respondents were asked to reflect on their current experiences with collaboration and suggest concrete opportunities for improving collaboration. Results: The results indicate that enhancing collaboration between the social and physical domains can be achieved by proceeding from the inhabitants’ perspective, as well as by encouraging aldermen and managerial personnel to take a more active and committed role in collaboration. This involves formulating and communicating a joint vision, in addition to guiding and facilitating collaboration through integrated assignments, forming multidisciplinary teams and appointing boundary-spanners. Civil servants see a clear role for themselves in the collaborative process. They recognise their own contributions to and obligations in enhancing collaboration by actively seeking contact, absorbing each other’s perspectives and pursuing common ground, starting today. Conclusion: There are many concrete opportunities to improve collaboration between the social and physical domains. This could be initiated immediately if civil servants, managers and aldermen approach collaboration as an essential part of their jobs and acknowledge the interdependency that exits.